2020
DOI: 10.1007/s00431-020-03616-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition and environmental factors associated with the development of atopic dermatitis in infancy: a prospective birth cohort study

Abstract: The influence of environmental factors on atopic dermatitis (AD) has been investigated in many cross-sectional studies. It remains however unclear if they could influence AD development early in life. This prospective birth cohort study aimed to monitor aspects of family lifestyle and child's nutrition within a Caucasian population and to assess its association with AD development over the first two years of life. Genetic predisposition was evaluated based on family history and profilaggrin genotyping. Of 149 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In our study, AD was frequently associated with a personal or family history of atopy. The frequent association between AD and a personal or family history of atopy is well documented in the literature [20,21].…”
Section: Discussionmentioning
confidence: 95%
“…In our study, AD was frequently associated with a personal or family history of atopy. The frequent association between AD and a personal or family history of atopy is well documented in the literature [20,21].…”
Section: Discussionmentioning
confidence: 95%
“…Roduit and co-workers showed that children’s risk of developing the early-persistent AD phenotype is five times greater in the case of parental allergies [ 77 ]. In addition, a birth cohort in Switzerland demonstrated that family history is the major risk factor for AD in Caucasians, regardless of even the most common filaggrin mutation, which was infrequent in this cohort [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Family history of atopic dermatitis can be a significant risk factor for the development of disease and onset in early infancy or childhood can persist into adulthood in severe cases. [46][47][48] Other risk factors include starting complementary food after the age of 6 months, skin problems in the first few months of life, and elevated blood eosinophils (defined as at least 5% of total leukocytes) at 4 weeks of age. 48,49 Males younger than 2 years are also at an increased risk of developing atopic dermatitis.…”
Section: Disease Backgroundmentioning
confidence: 99%